Risk in projekt management case of the factory of clothing inserts Camela S.A. in Wałbrzych, Poland - Gadzińska Justyna (My University, 2006)
The purpose of the thesis is analysis of risk in project management in case of the Factory Of Clothing Inserts CAMELA S.A. in Wałbrzych, Poland. The analysis allows understanding mechanisms accompanying engineering projects in the textile industry. In addition the analysis let the project manager recognizing specific management tools and activities that should be implemented during executing the project. There is no such an organization that controls risks. Still probability of occurring certain events may be estimated together with getting familiar with many different scenarios and arising consequences. This allows providing the mitigation plans and facing risk with deep knowledge about its sources. Therefore understanding risk management should be preceded with deep and wide knowledge about risk phenomenon, its measurement. In addition investor shall be aware of risk tolerance and social behaviors accompanying risk awareness. Above issues are presented in the first chapter of this thesis. Furthermore it provides essential matters in rationally taken decisions and presents complexity and difficulties in risk defining. The second chapter of the thesis analyzes micro- and macro environmental risks of the organization. Risk surrounding the projects and companies depends on today dynamically changing and fast developing macro environment. In response enterprises are required to implement changes in their micro environment faster and more effectively. Long term projects and changes are more risky than ever. Nowadays the world class companies consider project management as a powerful tool in achieving business goals and performance. Chapter three presents the basic conceptions and commonly known tools of Project Risk Management. This area of studies is still expanding and providing new methodologies. The workplace of project manager is highly skilled and advanced in technology. Today available software lets managing high complex and innovative projects, multidisciplinary teams and technological processes. The tools support SAP/ERP systems, complex form of work integration. However Project Management requires sophisticated management manners with changing organizational culture, management philosophy, leadership or motivation systems. In response to the business capabilities, Project Management evolved numerous of tools that deal with different companies and projects needs, limits and possibilities. The last chapter is a presentation of Camela Company and an introduction to the textiles and clothing industry. This part of the thesis establishes a view of Polish T/C market and allows compare it to the business situation of Camela Company.
Zarządzanie ryzykiem projektu na przykładzie Fabryki Wkładów Odzieżowych Camela S.A. w Wałbrzychu
Keywords: risk analysis; risk of the organisation; project management; managing risk; PMI approach; business risk